Differences in the delivery of motivational interviewing across three countries. Issue 3 (4th August 2022) - Kramer Schmidt, Lotte; Andersen, Kjeld; Søgaard Nielsen, Anette
Abstract: We do not know if the delivery of Motivational Interviewing (MI) differs across countries. In an international study targeting Elderly people with Alcohol Use Disorder, The Elderly Study, MI was part of the treatment applied. Treatment delivery was measured by means of the Motivational Interviewing Treatment Integrity code version 4 (MITI 4). Mixed effects models explored potential differences in delivery of MI between the countries. Delivery of MI differed significantly between participating countries: Denmark, Germany and the US. These findings are important to consider when comparing measures of MI integrity across studies from different cultures.